2008
DOI: 10.1007/s10549-008-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between farnesoid X receptor expression and cell proliferation in estrogen receptor-positive luminal-like breast cancer from postmenopausal patients

Abstract: International audienceThe farnesoid X receptor (FXR, NR1H4), a member of the nuclear receptor superfamily of ligand-dependent transcription factors, is normally produced in the liver and the gastrointestinal tract, where it acts as a bile acid sensor. It has been recently detected in breast cancer cell lines and tissue specimens. The expression of FXR was scored (0–8) by immunohistochemistry on 204 breast cancer samples and correlated with established cancer biomarkers. Moreover, the effect of the FXR activato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
53
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 45 publications
(60 reference statements)
10
53
1
Order By: Relevance
“…This is supported by previous studies showing that FXR expression is down-regulated in hepatitis C virus-induced liver fibrosis and human HCC specimen (31,32) as well as studies in colon (33) and breast (34) cancer. Our gene profiling analysis further revealed that FXR Ϫ/Ϫ mice had similar gene expression alterations as human HCC, indicating a potential role of FXR in human HCC development.…”
Section: Discussionsupporting
confidence: 85%
“…This is supported by previous studies showing that FXR expression is down-regulated in hepatitis C virus-induced liver fibrosis and human HCC specimen (31,32) as well as studies in colon (33) and breast (34) cancer. Our gene profiling analysis further revealed that FXR Ϫ/Ϫ mice had similar gene expression alterations as human HCC, indicating a potential role of FXR in human HCC development.…”
Section: Discussionsupporting
confidence: 85%
“…They also act as signaling molecules and metabolic regulators through the farnesoid X receptor (FXR) [35]. The FXR is expressed in breast ductal epithelial cells, human breast cancer cell lines [36] and normal breast tissue [37]. Therefore, while the changes observed here most likely reflect liver metabolism, systemic changes in the bile acid profile could also have an effect on breast tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobic BAs, such as deoxycholic acid (DCA) or lithocholic acid (LCA), have been reported to induce cell death in some cultured intestinal epithelial cell lines (7)(8)(9). Chenodeoxycholic acid (CDCA) enhances proliferation of certain cell lines (10), but the direct effect of each BA on epithelial cells depends on the cell line used. Moreover, in vivo, a variety of BAs exist at the same time in various tissues and intestinal contents, making it difficult to determine the precise influence of BAs on proliferation or survival of epithelial cells.…”
mentioning
confidence: 99%